Wind-Electric Power Potential Assessment for Three Locations in East Java-Indonesia - Ali Musyafa; I Made Yulistya Negara; Imam Robandi (IPTEK The Journal for Technology and Science, 2011)
This paper reports our effort to asses wind energy potentials for three locations in East Java. We used wind speed data over a period of almost 3 years, i.e. in period of June 2006 – August 2008. Data were taken from direct measurement in locations in East Java Province, i.e. Sampang (Madura), Juanda (Surabaya), and Sawahan (Nganjuk). The short-term of wind speed mean in monthly signifies to wind-speed value ”which parallels to the wind turbine power curve value” were used to estimate the annual energy output for a 1 MW installed capacity wind farm on the each site 100 of 10kW rated wind turbines were used in the analysis. The short term of wind speed mean at Surabaya and Nganjuk were 2.34, 3.03 and 1.97 m/s at 2 m Above Ground Level (AGL), respectively. In both locations, wind speeds were observed during the day time between 04.00 and 18.00 and relatively smaller ones between 19.00 and 03.00 period. Meanwhile, in Sampang (Madura) the higher wind speeds were observed between 20.00 and 06.00, and relatively smaller between 07.00 and 19.00 period. The 1 MW windfarm at Sampang, Surabaya and Nganjuk can produce 1.284; 1.199 and 1.008 MWh of electricity yearly, taking into consideration of the temperature adjustment coefficien of about 6 %. The plant capacity factor at Sampang, Surabaya and Nganjuk were found to be 30.02 %, 30.00 % and 30.01 % respectively. Additionally, it is noticed that these site can contribute to the avoidance of 0.904; 0.846 and 0.709 tons/year of CO2 equivalent Green House Gases (GHG) from entering into the local atmosphere, thus creating a clean and healthy athmosphere for local inhabitants.